2021
DOI: 10.1007/s10597-021-00789-7
|View full text |Cite
|
Sign up to set email alerts
|

Tele-Mental Health Utilization Among People with Mental Illness to Access Care During the COVID-19 Pandemic

Abstract: Shortly after the COVID-19 pandemic arrived at the United States, mental health services moved towards using tele-mental health to provide care. A survey about resilience and tele-mental health was developed and conducted with ForLikeMinds' members and followers. Correlational analysis was used to examine relationships between quantitative variables. A phenomenological approach was used to analyze open questions responses. Sixteen percent of participants were coping well with the pandemic; 50% were coping okay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 21 publications
5
36
0
Order By: Relevance
“… 21 Anxiety, major depressive disorder and post-traumatic stress disorder are the most common presenting conditions that may occur together or alongside pre-existing disorders. 22 This was probably the case for patients from the ADP cluster in the period immediately before the announcement of the lockdown, which shows an increase in absolute numbers. Second, the widespread implantation of telepsychiatry introduced new approaches to maintaining the patient–physician relationship.…”
Section: Discussionmentioning
confidence: 98%
“… 21 Anxiety, major depressive disorder and post-traumatic stress disorder are the most common presenting conditions that may occur together or alongside pre-existing disorders. 22 This was probably the case for patients from the ADP cluster in the period immediately before the announcement of the lockdown, which shows an increase in absolute numbers. Second, the widespread implantation of telepsychiatry introduced new approaches to maintaining the patient–physician relationship.…”
Section: Discussionmentioning
confidence: 98%
“…Not surprisingly, people using adaptive coping strategies were more likely to access mental health services during the lockdown [ 118 , 119 ]. However, it could be that people receiving adequate professional support are more likely to develop adaptive coping strategies [ 47 ]. On the other side, the adoption of avoidant coping strategies may influence the development of psychiatric symptoms, indirectly affecting access to mental health care services [ 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have assessed the use of mental health resources, especially during the first wave of the pandemic. Most evidence relies on qualitative reports from populations of service users or from data coming from limited settings, i.e., emergency departments [ 45 , 46 , 47 , 48 ]. An in-depth description of the use of mental health services during the COVID-19 pandemic is necessary in order to delineate new pathways to care and to develop supportive interventions for the general population [ 11 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was found in own our patient satisfaction survey results as well. One study found that approximately 8% of participants report that they would continue seeing their mental health provider by video after the stay at home recommendations are lifted (Costa et al, 2020 ). A more robust study found that a little over half of patients surveyed agreed they would consider remote treatment in the future (Guinart et al, 2021 ).…”
Section: Next Stepsmentioning
confidence: 99%